An introduction to programming with C++ - Zak, Diane (Boston, Massachusetts : Thomson Cource Technology, 2009)
An introduction to programming with C++, this book aims to motivate users by demonstrating why they need to learn the concepts and skills presented. It includes a lesson on .NET the teaches students how to use .NET C++ commands. It uses How To boxes to summarize important concepts and provide a quick reference for students.
1 An Introduction to Programming 2 Beginning the Problem-Solving Process 3 Completing the Problem-Solving Process and Getting Started with C++ 4 Variables, Constants, and Arithmetic Operators 5 The Selection Structure 6 More on the Selection Structure 7 The Repetition Structure 8 More on Repetition Structure 9 Value-Returning Functions 10 Void Functions 11 Arrays 12 String Manipulation 13 Sequential Access Files 14 Classes and Objects Appendix A C++ Keywords Appendix B ASCII Codes Appendix C Using Visual Studio 2005
Includes bibliographical references and index.
Keywords: C++ (COMPUTER PROGRAM LANGUAGE)